Aberrant distributions of nuclear pore complex proteins in ALS mice and ALS patients. (14th May 2017) - Shang, Jingwei; Yamashita, Toru; Nakano, Yumiko; Morihara, Ryuta; Li, Xianghong; Feng, Tian; Liu, Xia; Huang, Yong; Fukui, Yusuke; Hishikawa, Nozomi; Ohta, Yasuyuki; Abe, Koji
Graphical abstract: Highlights: Spatiotemporal expressions of nucleoporins in SOD1-Tg mice and ALS patients. Nucleoporins and TDP43 are co-localized in ALS. Nucleoporin dysfunctions are not specific only in C9-ALS but also in SOD1-ALS mice. Abstract: Nuclear pore complexes (NPCs) play important roles in traffic of molecules between the nucleus and cytoplasm, aberrant distributions of components of NPCs were demonstrated in C9orf72 amyotrophic lateral sclerosis (C9-ALS) patients, but it is elusive whether such abnormities are also the case with other cause of ALS disease. In the present study, we investigated the spatiotemporal distributions of RanGAP1 and 4 representative nucleoporins (GP210, NUP205, NUP107 and NUP50) of NPCs in human Cu/Zn superoxide dismutase-1 mutation transgenic (SOD1-Tg) mice and sporadic ALS patients. Compared with wild type (WT), these proteins displayed age-dependent and progressive nuclear precipitations, and cytoplasmic aberrant expressions in motor neurons of lumbar cord in SOD1-Tg mice from 10 to 18 weeks (W). Double immunofluorescent analysis showed abnormal nuclear retention and apparent co-localizations of RanGAPl with NUP205 and NUP205 with NUPl07, meanwhile, GP210 with NUP205 mainly co-localized in the nuclear envelope (NE) of motor neurons. Furthermore, RanGAP1, GP210 and NUP50 showed similarly abnormal nuclear precipitations and cytoplasmic upregulations in SOD1-Tg mice and ALS patients, moreover, aberrant co-localizations of RanGAP1 with TDP-43 and NUP205 with TDP-43 were also observed in motor neurons. The present study indicated that the mislocalization of these proteins of NPCs may underlie the pathogenesis of ALS both in SOD1-Tg mice and human sporadic ALS patients, and these dysfunctions may be a fundamental pathway for ALS that is not specific only in C9-ALS but also in SOD1-ALS, which may be amenable to pharmacotherapeutic intervention.